Kebijakan dan Upaya Progresif dalam Penanggulangan Stunting pada Balita - Sulfianti Fakhruddin; Andi Muti’ah Sari (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Stunting is a condition of growth failure in children under five due to chronic malnutrition characterized by their length or height being below the standard. Objective: Know progressive policies and efforts in overcoming stunting in toddlers. Method: Qualitative research with 16 informants, including ordinary and key informants. Results: Show that aggressive actions in overcoming stunting are minimal because officers' knowledge, parenting, and role are still shallow. Conclusion: That progressive efforts to combat stunting still need to be improved regarding maternal knowledge about healthy and nutritious food for toddlers. Policymakers to play a proactive role in tackling stunting through education, counselling, and empowerment to mothers of toddlers so that they can understand the causes and risks if their children suffer from stunting.